How do care-provider and home exercise program characteristics affect patient adherence in chronic neck and back pain: a qualitative study - de Oliveira Sousa Silvana L; Jimeno-Serrano Francisco J; Montilla-Herrador Joaquina; Gascón-Cánovas Juan J; Medina-Mirapeix Francesc; Escolar-Reina Pilar; del Baño-Aledo M Elena; Lomas-Vega Rafael (BMC, 2010)
Abstract Background The aim of this study is to explore perceptions of people with chronic neck or low back pain about how characteristics of home exercise programs and care-provider style during clinical encounters may affect adherence to exercises. Methods This is a qualitative study consisting of seven focus groups, with a total of 34 participants presenting chronic neck or low back pain. The subjects were included if they were receiving physiotherapy treatment and were prescribed home-based exercises. Results Two themes emerged: home-based exercise programme conditions and care provider's style. In the first theme, the participants described their positive and negative experiences regarding time consumption, complexity and effects of prescribed exercises. In the second theme, participants perceived more bonding to prescribed exercises when their care provider presented knowledge about the disease, promoted feedback and motivation during exercise instruction, gave them reminders to exercise, or monitored their results and adherence to exercises. Conclusions Our experiential findings indicate that patient's adherence to home-based exercise is more likely to happen when care providers' style and the content of exercise programme are positively experienced. These findings provide additional information to health care providers, by showing which issues should be considered when delivering health care to patients presenting chronic neck or back pain.